Food safety and sustainability: An exploratory approach at the level of the Romanian wine production companies - Gheorghe Epuran; Gabriel Brătucu; Oana Bărbulescu; Nicoleta Andreea Neacşu; Anca Madar (Amfiteatru Economic Journal, 2018)
Food safety represents a current topic, with significant implications and diverse approaches within the specialized literature. In the context of globalization and integration of agricultural markets, the necessity of guaranteeing food safety is imperative for the functionality of contemporary agricultural systems. The radical transformation of the national agricultural systems as a result of the influences imposed by the convergence with the requirements and directions of the European agricultural model entails a significant change for the markets of agri-food products, affecting the food trade, its structure and, implicitly, food safety. In this context, the main objective of the present paper is to examine food safety in Romania using an econometric approach to the phenomenon. Nine fundamental variables are considered, for which the causal relationship between food safety and the exogenous variables taken into analysis is tested. The time frame for data availability for all the variables is 1990-2011. The obtained results highlight the transformations of paradigm of the national agricultural model from the perspective of the dimensions regarding food safety, confirming results from previous studies.
Keywords: L15; L66; M31; Q01; Q13; Q18; 330; sustainable development; food safety; European legislation; wine quality; wine industry; marketing strategies; education; Machine to Machine; Internet of Things